Evaluation of Public Satisfaction with OpenSID-Based E-Government Services at the Village Level Using the Customer Satisfaction Index and e-GovQual Dimensions - Adib Pakarbudi; Krisna Febriansyah (Journal of Information Technology and Cyber Security, 2026)
E-Government is an important innovation in improving the efficiency, transparency, and quality of public services, including public services at the village government level. However, the implementation of e-government in Purworejo, Pungging District, Mojokerto Regency still faces various problems, such as low digital literacy and limited user support features. This condition is in line with the findings of the UN e-Government Survey 2024 which stated that approximately 22.4% of the global population is still lagging behind in accessing digital services due to infrastructure and literacy gaps, especially in developing regions. This study aims to analyze the level of public satisfaction with e-government services in the OpenSID-based village service system using the Customer Satisfaction Index (CSI) method. This study used a quantitative approach by collecting data through questionnaires from 273 respondents. Satisfaction measurements were carried out based on six dimensions of e-Government Quality (e-GovQual): Ease of Use, Trust, Functionality of the Interaction Environment, Reliability, Content and Appearance of Information, and Citizen Support. The results showed a CSI value of 70%, which is included in the satisfied category. The Trust dimension obtained the highest score of 0.65, followed by Reliability, Functionality of the Interaction Environment and Ease of Use at 0.60 and Content and Appearance of Information at 0.58. In contrast, the Citizen Support dimension had the lowest score of 0.46 and is an aspect that requires attention and improvement. This study provides an empirical contribution in the evaluation of e-government services at the village level by identifying priority service dimensions, especially Citizen Support, as a basis for improving the quality of digital public services and demonstrating the effectiveness of integrating the e-GovQual model and Customer Satisfaction Index in the context of village government.